Adult education on digital, health and data literacy for citizen empowerment: the TRIO project - Natália, Machado; Carina, Dantas; Joana, Vieira (Magyar Gerontológia, 2023)
Older adults often live with chronic conditions for extended periods, leading them to make daily decisions about managing their illnesses, including lifestyle choices, diet, and medications (Alqahtani &, 2022). Even before the rapid growth of digital health, this was already a challenge they faced. However, the swift expansion of digital health has introduced certain advancements that have somewhat eased health management for caregivers and older adults. On the other hand, while digital health literacy empowers individuals to adopt healthier lifestyles, people in vulnerable conditions, which often includes older adults (Jung , et al., 2022), namely those with limited socioeconomic resources, encounter difficulties in keeping up with technological progress.